Strategic Approaches to Student Involvement in Formative Assessment: Insights From Qualitative Interviews - Delavarpour, Pooya; Safarnejad, Elham (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore the strategic approaches employed by educators to meaningfully involve students in formative assessment within the school system of Tehran, Iran. A qualitative research design was adopted, utilizing semi-structured interviews with 24 educators from various public and private schools in Tehran. Participants were selected through purposive sampling based on their active engagement in assessment practices. Data collection continued until theoretical saturation was achieved. Interviews were transcribed verbatim and analyzed thematically using NVivo software. Thematic analysis followed Braun and Clarke’s six-step framework, with open codes developed inductively and refined into broader subthemes and main themes. Analysis revealed three overarching themes: pedagogical strategies for engagement, psychological enablers of participation, and institutional and cultural influences. Within these, teachers reported using student-centered goal setting, peer assessment, dialogic teaching, and digital tools to increase student participation. Emotional safety, trust, and a growth-oriented mindset were identified as psychological preconditions for involvement. Additionally, the implementation of formative practices was influenced by school culture, leadership support, curricular flexibility, and parental expectations. Teachers who had access to professional development and institutional support demonstrated greater innovation in engaging students. Despite systemic barriers, educators employed context-sensitive strategies to foster student agency and ownership in assessment. The study highlights that effective student involvement in formative assessment is a multifaceted process requiring intentional pedagogy, emotional support, and enabling institutional environments. Findings suggest the need for professional learning, leadership backing, and cultural alignment to enhance participatory assessment practices. The research offers practical implications for teacher training, curriculum design, and school policy aimed at promoting formative assessment cultures.